ANCA-Associated Vasculitides and Hematologic Malignancies: Lessons from the Past and Future Perspectives. (6th May 2019) - Folci, Marco; Ramponi, Giacomo; Shiffer, Dana; Zumbo, Aurora; Agosti, Michele; Brunetta, Enrico
Abstract : The purpose of this paper is to collect and summarize all evidences relating to an association between ANCA-associated vasculitides (AAVs) and hematologic malignancies, in the form of either a paraneoplastic vasculitis or leukemias and lymphomas developing on a preexisting vasculitis. Additionally, the role of cyclophosphamide in vasculitis treatment has been assessed and compared to rituximab. Paraneoplastic AAV seems to be an uncommon presentation of hemopathies. Hematologic malignancy risk in AAV is more likely to be increased by cyclophosphamide, although not yet definitely proven. Furthermore, the pathogenesis of ANCA-associated vasculitis has been reviewed with particular emphasis on the role of proteinase 3 (PR3) in fuelling granulomatosis with polyangiitis (GPA) inflammation. PR3 is a bactericidal protein expressed by neutrophilic granules and on their plasma membrane. Derangements in its expression and function have been linked to leukemias and GPA alike. PR3-derived PR1 peptide is being studied as an immunotherapy target in leukemia and multiple myeloma. This study is aimed at bringing together various evidences from the field of immunological and hematological research, at exposing contradictions, and at revealing novel insights on the association between ANCA-associated vasculitis and hematologic malignancies.